PENERAPAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 DIBANDINGKAN PELAKSANAAN PAJAK PENGHASILAN PADA PT GLOBAL BINTANG UTAMA JAKARTA - AA Supardi AA Supardi; Ari Samto (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
This study was conducted to determine how much influence the implementation of the before and after implementation of Government Regulation No. 46 Year 2013 on PT Global Bintang Utama Jakarta. In mid-2013 the Government issued Government Regulation No. 46 Year 2013 is localized for enterprises that have a gross income below Rp.4.800.000.000 (four billion, eight hundred million rupiah). Government Regulation No. 46 Year 2013 issued not to replace Law No. 36 In 2008, these regulations are specialized for small and medium enterprises (SMEs). In Act No. 36 of 2008 by Government Regulation No. 46 Year 2013 there is a difference for the count, deposit and reporting of tax payable on an enterprise and differences in tax treatment, these rules in terms of taxation policy, the tax laws and tax administration in accordance with applicable tax regulations.